Impact of the ‘Brussels Effect’ on Indonesian Palm Oil Exports to the European Union - Trystanto (Journal of World Trade Studies, 2021)
Even though the EU may lack sufficient coercive economic and military power, it is considered to be one of the "regulatory powers" of the world with the capacity to export its laws and regulations outside its frontier. However, this exercise of regulatory power has resulted in conflicts with other nations around the world as it could directly affect other nations' trade, most notably Indonesia's palm oil exports to the EU. This study examines the effect of the EU's regulatory powers (i.e., the 'Brussels effect') on Indonesia's palm oil export to the EU. This study uses a comparative and descriptive approach by comparing Indonesia's palm oil exports to the EU and charting the amount and dollar value of palm oil exports from Indonesia to the EU from the year 2013 until 2019. This article finds that the Brussels effect has reduced 42% of Indonesian palm oil exports to the EU in 2016, compared to the previous year. In spite of this, the total volume of Indonesia's palm oil export remains relatively unaffected, although the dollar value has not yet recovered due to the fluctuating nature of crude palm oil prices.